Typological characterization of dual-purpose cattle farming in Santiago Pinotepa Nacional, Oaxaca, Mexico: Tipología de la ganadería doble propósito - Cisneros-Saguilán, Pedro; Martínez-Vasquez, Jaime; de la Rosa-Galindo, Arturo; Candelaria-Martínez, Bernardino; Portillo-Salgado, Rodrigo (Ecosistemas y Recursos Agropecuarios, 2024)
In Mexico, dual-purpose cattle farming (DPCF) is one of the most relevant small-scale production systems in rural areas; however, it presents high variability in terms of its socioeconomic, productive and technological parameters. The objective of this study was to characterize the DPCF in the municipality of Santiago Pinotepa Nacional, Oaxaca, Mexico, and to establish a representative typology of producers. To this end, a survey was applied to 155 producers, using a questionnaire that included quantitative and qualitative variables classified into four sections: social, productive, economic and technological. The information collected was analyzed using descriptive statistics, multivariate analysis techniques and analysis of variance. The principal component analysis revealed four factors that explained 78.27% of the original variability, and were related to the productivity and size of the ranch (F1), the social-cultural condition of the producer (F2), the productive efficiency of the ranch (F3), and family aspects of the producer (F4). The hierarchical cluster analysis classified producers into three groups, referred to as traditional (89.03%), in transition (8.38%), and commercial (2.5%). The differences between the producer groups identified are in terms of ranch area, herd size, milk production per week, number of calves sold per year and annual income.